Similarity and difference in fee-paying and no-fee learner expectations, interaction and reaction to learning in a massive open online course. Issue 4 (19th May 2017) - Cross, Simon; Whitelock, Denise
ABSTRACT: The new pedagogical opportunities that massive open online course (MOOC) learning environments offer for the teaching of fee-paying students on university-accredited courses are of growing interest to educators. This paper presents a case study from a postgraduate-taught course at the Open University, UK, where a MOOC performed the dual role of a core teaching vehicle for fee-paying students and also as a "free-to-join" course for open learners. An analysis of survey data revealed differences between the two groups in respect to prior experience, knowledge, expectations and planned time commitment. The nature and experience of interaction was also examined. Fee-paying student feedback revealed four conditions in which MOOCs could be considered a pedagogic option for taught-course designers. These are: when there is a subject need; when used to achieve learning outcomes; when there is acknowledgement or compensation for the financial disparity; and when issues of transition and interaction are supported.